Elementary principals' social construction of parents of color and working class parents: Disrupting or reproducing conflicting and deficit orientations of education policy? - Melanie Bertrand; Rhoda Freelon; John Rogers (Arizona State University, 2018)
School principals, contending with competing characterizations of parents in education policy and society, may view parents in a number of ways. Two common understandings portray parents as authentic partners or, in contrast, simply supporters of the school's agenda. This paper explores these characterizations by considering the possible link between principals' understandings of parents and their approaches to parent engagement and/or shared decision making, especially in light of the ways that the social context and education policy construct parents of color and working class parents as deficient. We use the lens of social construction of target populations to add to the currently minimal literature that directly examines principals' views of parents. We report findings of a multi-phase analysis of surveys of 667 elementary principals in the state of California and interviews with a subgroup of 34 of these principals. We explore how principals structured parent engagement and conceived of the goals and rationales for parent workshops, illustrating how they socially constructed the target population of parents, particularly parents of color and working class parents. We find that principals often constructed parents in terms of deficiencies and as needing to learn to better support school goals. Our findings have profound implications for advancing equity in schools.